VD_FINDINFO HC / 2020 / 566 vom 25. Mai 2020 - VD Tribunal cantonal (2020)
INVITATION, ASSEMBLÉE GÉNÉRALE, ORGANEPERSONNE MORALE, SOCIÉTÉ ANONYME, ORDRE DU JOUR, ABUS DE DROIT | 699 CO, 312 al. 1 CPC (CH)